Milk Fat Globule Membrane Alleviates Short Bowel Syndrome-Associated Liver Injury in Rats Through Inhibiting Autophagy and NLRP3 Inflammasome Activation - Yu, Zhicai; Huang, Shanshan; Li, Ying; Niu, Yang; Chen, Honghao; Wu, Jiang (Frontiers in Nutrition, 2022)
Background: The milk fat globule membrane (MFGM), a tri-layer membrane structure surrounding the milk fat globule, has been shown to have immune-modulating properties. This study aimed to investigate the effects of MFGM supplementation in a rat model of short bowel syndrome (SBS) associated liver disease and its possible mechanisms. Materials and Methods: 21 male Sprague-Dawley rats were randomly divided into three groups: Sham, SBS (underwent massive small bowel resection), and SBS+MFGM (SBS rats supplemented with 1.5g/kg/d MFGM). Liver pathology, myeloperoxidase (MPO) staining, serum levels of aspartate aminotransferase (AST)/alanine aminotransferase (ALT), endotoxin concentration, protein expression of autophagy and nucleotide binding oligomerization domain, leucine-rich repeat and pyrin domain-containing protein 3 (NLRP3) pathway in the liver tissue were measured. Results: Both SBS and SBS+MFGM groups had higher serum levels of ALT and liver endotoxin levels than the Sham group (P<0.05), with no difference detected between each other. Compared with the SBS group, the SBS+MFGM group showed lower liver pathology scores of steatosis and inflammation, less MPO positive cells and reduced expressions of NLRP3, apoptosis-associated speck-like protein containing a CARD (ASC), Caspase-1, interleukin (IL)-1β(P<0.05) in the liver. Additionally, the expression of Beclin-1 and microtubule-associated protein1 light chain 3(LC3) B, the fluorescence intensity of NLRP3 and LC3B in the SBS + MFGM group were lower than the SBS group (P< 0.05). The LC3B expression was positively correlated with the NLRP3 level. Conclusion: Enteral supplementation of MFGM help to alleviate liver injury in SBS rats, which might be related to inhibition of aberrant activation of autophagy and NLRP3 inflammasome pathways.